The Respirator Fit Capability Test: Enhancing the Efficacy of Filtering Facepiece Respirators - Coffey, Christopher (Synergist (Akron), 2019)
When NIOSH promulgated its Respiratory Protective Devices rule in 1995 (Title 42 code of Federal Regulations, Part 84), which specified approval standards for respirators, no test for evaluating the fitting characteristics of filtering facepiece respirators was included. The consequences of the lack of a fit test in 42 CFR 84 included the approval of devices that did not fit the general respirator-wearing population very well, higher costs for conducting the OSHA-required fit test, and the potential for wearing to pass a fit test in error. Today, the need still exists for a fit test for use by manufacturers of filtering facepiece respirators and conformity assessment organizations.